2020
DOI: 10.1101/2020.12.14.20245266
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Efficacy and Safety of Indomethacin in Covid -19 patients

Abstract: Background Indomethacin, a well-known non-steroidal anti-inflammatory drug (NSAID), has in addition broad spectrum anti-viral activity in the laboratory including on SARS-Cov-2 virus. This trial is to observe the likelihood of efficacy and safety of Indomethacin in treating RT-PCR positive Covid patients Materials and Methods The study was done in two groups. In the first group of the study, where mild and moderate patients were involved, Propensity Score Matching was used as a methodology to compare Indo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…The results are similar to our earlier study based on propensity score matching [27]. The median time for becoming afebrile, cough reduction and myalgia relief in the indomethacin arm was four and three and four days respectively.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The results are similar to our earlier study based on propensity score matching [27]. The median time for becoming afebrile, cough reduction and myalgia relief in the indomethacin arm was four and three and four days respectively.…”
Section: Discussionsupporting
confidence: 89%
“…Rajan et al [21] conducted one of the first indomethacin trials. Using the data from an open-label single-arm data for indomethacin, they showed the effect of indomethacin as a treatment option by matching propensity score with retrospectively collected data on paracetamol.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, there is evidence that aspirin may reduce plasma levels of pro-inflammatory cytokines (37), and lower the risk of in-hospital mortality in a large cohort of patients hospitalized with COVID-19 (38), supporting the use of this drug in the early stages of COVID-19 at home when needed. In the future, other NSAIDs, such as indomethacin, which also lowers IL-6 in SARS-CoV-2 patients (39), could be proposed as an alternative treatment for early COVID-19 symptoms at home, as anticipated by a recent small Indian study (40).…”
Section: Discussionmentioning
confidence: 99%
“…No patients in the second group required mechanical ventilation, and no adverse effects were seen with indomethacin administration. Hence, the authors suggested that indomethacin added to standard care offers more rapid symptomatic relief and prevents progression of pneumonia and therefore, replacement of paracetamol with indomethacin should be taken into consideration [ 22 ].…”
Section: Evidence For Use Of Indomethacin In Covid-19mentioning
confidence: 99%